The World’s Oldest Living Proverb Discovered Thriving in Ethiopia - Unseth, Peter (Aethiopica, 2018)
The world’s oldest living proverb, from around 3,800 years ago, is found on a tablet from the Assyrian empire. The proverb has been documented from later eras, northwest from the Middle East up into Europe, as far northwest as Britain. Evidence is given here now demonstrating that the proverb is also found to the south of the Middle East, in Ethiopia. In some places, a cat is substituted for the dog, but the Ethiopian evidence indicates that the dog version of the proverb is original.